Struktur Bawah Permukaan pada Lokasi Rencana Pembangunan Rumah Sakit Muhammadiyah Kota Bengkulu dengan Metode seismik MASW Secara 2 Dimensi - Lubis, Ashar Muda; Satriani, Bella; Lizalidiawati, Lizalidiawati; Samdara, Rida (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2020)
A study on the subsurface structure has been conducted using the multichannel analysis of surface wave (MASW) method near Tugu Hiu, Bengkulu City, the location where Muhammadiyah hospital will be built. We aimed to determine the subsurface structure in 2-Dimension (2D) to classify soil type on the location. The data were measured with seismograph PASI 16S24-P using 24 geophones for a track of 72 m of total length and 1.5 m of intervals. The seismic data were processed by using seismic ParkSeis software. The results show that shear wave velocity (Vs) is 800-1200 m/s at a depth of 1-5 m, indicating this layer is filled by rock type (unsaturated). At a depth of 6-8 m below surface, Vs value decreases to 400-500 m/s which may indicate that the soft rock type fills the layer. The results of this study provide a high level of confidence, about 80-100%, in the Vs value. Thus, we suggest for the foundation of hospital construction, the pillars for construction must be for more than 10 m in depth with a solid concrete foundation. This to ensure the foundation can withstand the building in case of shake during an earthquake.